The landscape of RNA-chromatin interaction reveals small non-coding RNAs as essential mediators of leukemia maintenance - Yun, Haiyang; Zoller, Julian; Zhou, Fengbiao; Rohde, Christian; Liu, Yi; Blank, Maximilian Felix; Göllner, Stefanie; Müller-Tidow, Carsten (Leukemia, 2024)
RNA constitutes a large fraction of chromatin. Spatial distribution and functional relevance of most of RNA-chromatin interactions remain unknown. We established a landscape analysis of RNA-chromatin interactions in human acute myeloid leukemia (AML). In total more than 50 million interactions were captured in an AML cell line. Protein-coding mRNAs and long non-coding RNAs exhibited a substantial number of interactions with chromatin in cis suggesting transcriptional activity. In contrast, small nucleolar RNAs (snoRNAs) and small nuclear RNAs (snRNAs) associated with chromatin predominantly in trans suggesting chromatin specific functions. Of note, snoRNA-chromatin interaction was associated with chromatin modifications and occurred independently of the classical snoRNA-RNP complex. Two C/D box snoRNAs, namely SNORD118 and SNORD3A, displayed high frequency of trans-association with chromatin. The transcription of SNORD118 and SNORD3A was increased upon leukemia transformation and enriched in leukemia stem cells, but decreased during myeloid differentiation. Suppression of SNORD118 and SNORD3A impaired leukemia cell proliferation and colony forming capacity in AML cell lines and primary patient samples. Notably, this effect was leukemia specific with less impact on healthy CD34+ hematopoietic stem and progenitor cells. These findings highlight the functional importance of chromatin-associated RNAs overall and in particular of SNORD118 and SNORD3A in maintaining leukemia propagation.
Gesehen am 08.01.2025